2016
DOI: 10.1097/jom.0000000000000865
|View full text |Cite
|
Sign up to set email alerts
|

Costs and Work Loss Burden of Diagnosed Opioid Abuse Among Employees on Workers Compensation or Short-term Disability

Abstract: Opioids are commonly prescribed to employees with injury-related WC/STD claims. Employers may benefit from proactively addressing the issue of opioid abuse in these populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…Two studies reported data on annual inpatient stays over a 12-month follow-up period; the average number of annual inpatient stays was 0.8–1.9 for abusers and 0.1–1.3 for controls, respectively [ 34 , 35 ]. These studies similarly reported that abusers had a significantly higher average number of hospitalization days over a 12-month follow-up period when compared with controls (4.8 and 10.6 days for abusers and 0.5 and 5.2 days for non-abusers, respectively) [ 34 , 35 ]. In addition, the average number of mental health-related hospitalization days during the same period was significantly greater for abusers compared with controls (3.2 vs 0.0; p < 0.0001) [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two studies reported data on annual inpatient stays over a 12-month follow-up period; the average number of annual inpatient stays was 0.8–1.9 for abusers and 0.1–1.3 for controls, respectively [ 34 , 35 ]. These studies similarly reported that abusers had a significantly higher average number of hospitalization days over a 12-month follow-up period when compared with controls (4.8 and 10.6 days for abusers and 0.5 and 5.2 days for non-abusers, respectively) [ 34 , 35 ]. In addition, the average number of mental health-related hospitalization days during the same period was significantly greater for abusers compared with controls (3.2 vs 0.0; p < 0.0001) [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported the proportion of abusers with 1 or more inpatient visits during a 12-month follow-up period following diagnosis, which varied from 34.2 to 57.7% for abusers and 7.3 to 25.5% for controls [ 24 , 34 ]. The average proportion of patients with an inpatient visit was highest among Medicare members aged < 65 years (43.3%), compared to privately insured US patients (40.2%) and Medicare members aged ≥ 65 years (34.2%) [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations